Patent ductus arteriosus shunting direction and diameter predict inpatient outcomes in newborns with congenital diaphragmatic hernia - Bao, Min; Wu, Tao; Guo, Jinghui; Wang, Ying; Cao, Aimei; Liu, Chao; Wei, Yandong; Zheng, Chunhua; Shi, Lin; Ma, Lishuang (Frontiers in Pediatrics, 2023)
OBJECTIVE: To evaluate whether the patent ductus arteriosus (PDA) can serve as a predictive factor for inpatient outcomes in congenital diaphragmatic hernia (CDH) patients.METHODS: A retrospective cohort study was conducted on 59 CDH patients at the Capital Institute of Pediatrics from January 2020 to August 2022. Echocardiography was performed at least three times: within 2-3 hours after birth, pre-operatively, and post-operatively of CDH surgery. Based on the direction of the PDA shunt in the first echocardiogram, patients were classified into three groups: leftto-right shunting or closed PDA (L-R), bi-directional shunting, and right-to-left shunting (R-L). RESULTS: The mortality rate was 15.3% (9/59), with all non-survivors having R-L shunting and group mortality of 39.1% (9/23). The direction of the PDA shunt was significantly associated with the duration of ventilation and length of hospital stay (p<0.05). Decreased PDA diameter or preoperative shunting direction change towards L-R or bi-directional shunting were associated with higher survival rates, while increased PDA diameter or continuous R-L shunting were associated with higher mortality rates. Pre-operative PDA shunt direction, PDA size after birth and before surgery, gestational age of diagnosis, and shortening fraction before surgery were significantly correlated with patient outcomes. The direction of the preoperative PDA shunt was the most relevant factor among these relationships (p=0.009, OR 20.6, CI 2.2~196.1). CONCLUSION: Our findings highlight the importance of monitoring changes in PDA shunt directionality and diameter in the early stage after birth, as these parameters may serve as valuable predictors of patient outcomes.